A study of role of doppler in gestational hypertension and perinatal outcome - Chavda, Anjali R.; Shah, Parul T.; Patel, Rina V.; Patel, Hemali N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Hypertensive disorder of pregnancy is one of the most common complications that affect the human pregnancy. Hence it is important to identify women at risk of developing gestational hypertension or preeclampsia, its early diagnosis and subsequent consequences due to uteroplacental insufficiency with help of Doppler ultrasound, to improve perinatal outcome. The objective of this study was to study the application of Doppler ultrasound with analysis of blood flow velocity waveform in gestational hypertension and to examine and study the perinatal outcome in pregnancy with altered Doppler indices. Methods: A prospective study was carried out in 50 antenatal patients diagnosed to have gestational hypertension during a period of 12 months to evaluate the role of color Doppler imaging in gestational hypertension in patients more than 28 weeks of gestation, the initial scan was performed immediately after the diagnosis. This study analyzed the blood flow in umbilical artery, maternal uterine artery and fetal middle cerebral artery using Doppler ultrasound. Results: In this study approximately 76% of cases were found in 20-30 years group. 58% showed abnormal umbilical artery Doppler while 42% women had normal umbilical artery Doppler. In this study 23 cases had cerebro-placental index <1 and 27 cases had cerebro-placental index >1. Cases with cerebro-placental index <1 had various complications like preterm delivery, low birth weight, increased chances of still birth, intra uterine death (IUD), increased NICU admission. In this study 31 cases had abnormal uterine artery Doppler which accounts for 62% of total cases, while 38% had normal uterine artery Doppler. Conclusions: Doppler ultrasound can reliably predict any adverse fetal outcome in hypertensive pregnancies and can be a useful tool for decision making in appropriate timing of intervention for delivery.